Ultrafast removal of radioactive strontium ions from contaminated water by nanostructured layered sodium vanadosilicate with high adsorption capacity and selectivity - Zhang, Xiaoyuan (2022)
Layered sodium vanadosilicates was synthesized for removing soluble strontium ion (Sr2+) from simulated radioactive wastewater. SEM, EDS and TEM images indicated that layered sodium vanadosilicates had a nanostructure with flake-like shape providing an extremely large surface area. XRD, FTIR and XPS analyses further revealed a framework structure of adsorbent consisting of corner-sharing SiO4 tetrahedra and VO6 octahedra, with sodium ion being the major cation in the synthesized nanostructured layered sodium vanadosilicate. This study for the first time showed ultrafast adsorption of Sr2+ by nanostructured layered sodium vanadosilicates in a time frame of seconds with a high adsorption capacity of 174.3 mg/g estimated from Langmuir isotherm. It was found that about 99.0% of Sr2+ at an initial concentration of 5.00 mg/L and adsorbent dosage of 0.5 g/L could be removed within several seconds. The kinetic analysis further revealed that pseudo-second-order instead of pseudo-first-order kinetics could satisfactorily describe the observed ultrafast removal of Sr2+. In particular, the nanostructure layered sodium vanadosilicates exhibited an excellent affinity to Sr2+ over a wide pH range of 3-11. It was also demonstrated that the working mechanisms of nanostructured layered sodium vanadosilicates for Sr2+ removal mainly included surface electrostatic interaction and ion-exchange with sodium ion. Furthermore, nanostructure layered sodium vanadosilicates had significant advantages for Sr2+ removal compared with other adsorbents. Consequently, it is reasonable to expect that nanostructured layered sodium vanadosilicates synthesized in this study could be considered as a promising adsorbent for ultrafast and high-efficiency removal of radioactive Sr2+ from radioactive wastewaters.